A Modified Analytical Heat Source Model for Numerical Simulation of Temperature Field in Friction Stir Welding - Xiangqian Liu; Yan Yu; Shengli Yang; Huijie Liu (Advances in Materials Science and Engineering)
In the conventional analytical model used for heat generation in friction stir welding (FSW), the heat generated at the pin/workpiece interface is assumed to distribute uniformly in the pin volume, and the heat flux is applied as volume heat. Besides, the tilt angle of the tool is assumed to be zero for simplicity. These assumptions bring about simulating deviation to some extent. To better understand the physical nature of heat generation, a modified analytical model, in which the nonuniform volumetric heat flux and the tilt angle of the tool were considered, was developed. Two analytical models are then implemented in the FEM software to analyze the temperature fields in the plunge and traverse stage during FSW of AA6005A-T6 aluminum hollow extrusions. The temperature distributions including the maximum temperature and heating rate between the two models are different. The thermal cycles in different zones further revealed that the peak temperature and temperature gradient are very different in the high-temperature region. Comparison shows that the modified analytical model is accurate enough for predicting the thermal cycles and peak temperatures, and the corresponding simulating precision is higher than that of the conventional analytical model.